Three cups of tea - Thomson, Sarah L.; Mortenson, Greg.; Relin, David Oliver (New York Puffin Books, 2009)
An adaptation of the bestselling book about the American Greg Mortenson's building of over 60 schools in Pakistan and Afghanistan.
Failure -- Wrong side of the river -- I'm going to build you a school -- Growing up -- 580 letters, one check -- Hard way home -- Korphe at last -- Bridge before a school -- Hunting Ibex -- Building bridges -- Six days -- Beginnings -- Haji Ali's lesson -- Smile should be more than a memory -- Picture -- New schools-and more -- Running from war -- Too much to do -- Village called New York -- Afghanistan -- First educated women in Korphe -- Stones into schools.
"One man's journey to change the world, one child at a time"--Cover.
Includes a reader's guide and an inteview with Amira Mortenson, Greg Mortenson's daughter.
Keywords: Mortenson, Greg -- Juvenile literature; Mortenson, Greg; Girls' schools -- Pakistan -- Juvenile literature; Girls' schools -- Afghanistan -- Juvenile literature; Humanitarian assistance, American -- Pakistan -- Juvenile literature; Humanitarian assistance, American -- Afghanistan -- Juvenile literature